EXPRESSION OF COLLAGENS IN THE DAMAGE AREA AT ABDOMINAL ADHESIONS - I. A. Shurygina; M. G. Shurygin; L. V. Rodionova; E. E. Chepurnykh; N. I. Ayushinova (Acta Biomedica Scientifica)
Background. Postoperative adhesions are a serious problem in surgery. However, at the present time molecular mechanisms of the adhesion process are insufficiently studied. Aim. To study the dynamics of expression of genes encoding the synthesis of collagen in case of damage to the serosa on the example of the peritoneum in conditions of aseptic inflammation. Materials and methods. Aseptic inflammatory process in the abdominal cavity was modeled (Wistar rats, n = 40). A micro- and macroscopic picture of the damage area was studied. Immunofluorescent staining for Type I collagen (Col 1A1) was performed. The expression of genes encoding collagen of different types was evaluated using the RT2-Profiler PCR kit Array Rat Wound Healing. Results. It has been established that the adhesion process with peritoneal damage in aseptic conditions reaches its maximum by the 30th day of observation. The same period coincides with the maximum of collagen synthesis in fibroblasts in the repair area, revealed by immunofluorescence study. The interrelation of synthesis of type I and III collagens went as expected - the onset of expression of type III collagen (from day 3) is ahead of the expression of collagen type I (from day 7). Peak gene expression of collagens type I, Alpha-1 and -2; type III Alpha-1, type IV Alpha-1 and -3, type V Alpha-1, -2 and -3; type XIV Alpha-1 (Col14a1) falls on the 14th day. For the first time, active involvement of type V alpha-3 collagen in the adhesion process was noted - we detected both early (from day 1) and maximum intensive (up to 166.96 times increase in comparison with intact animals). Conclusion. Perhaps, the hyperexpression of collagen V alpha-3 that we revealed is an important link in the pathogenesis of adhesion in the abdominal cavity.